Special Issue: Micro-foundations of macroeconomics: how important are they? - Philip Arestis; Jesus Ferreiro (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
Editorial to the Special Issue - The Department of Applied Economics V of the University of the Basque Country (UPV/EHU) and the Cambridge Centre for Economic and Public Policy, Department of Land Economy of the University of Cambridge, organized the 10th International Conference entitled Developments in Economic Theory and Policy. The Conference took place in Bilbao (Spain) on 27 and 28 June 2013. In this issue of the European Journal of Economics and Economic Policies: Intervention (EJEEP), the papers of the special session, 'Micro-foundations of macroeconomics: how important are they?' are published.
Keywords: 330